2019
DOI: 10.1016/j.joco.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy for eyelid and anterior orbital venous-lymphatic malformation

Abstract: Purpose To assess the efficacy of sclerotherapy with sodium tetradecyl sulfate (STS; Fibrovein 1%) in superficial periocular venous and lymphatic malformations. Methods Eleven patients with low-flow venous and lymphatic malformations with extension predominantly to the eyelids, conjunctiva, and anterior orbit were selected. Sclerotherapy with STS was undertaken as an office-based procedure without any radiological guidance. Injections were repeated every 4 weeks until d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…When this agent is injected intravenously, it causes intimal inflammation and thrombus formation, which usually occlude the injected vein. Following the formation of fibrous tissue, the vein is partially or completely obliterated, which may or may not be permanent [ 13 , 14 ]. Bleomycin is a cytostatic antineoplastic agent that inhibits the rapamycin (mTOR) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When this agent is injected intravenously, it causes intimal inflammation and thrombus formation, which usually occlude the injected vein. Following the formation of fibrous tissue, the vein is partially or completely obliterated, which may or may not be permanent [ 13 , 14 ]. Bleomycin is a cytostatic antineoplastic agent that inhibits the rapamycin (mTOR) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This agent was chosen due to its relative high potency compared to various other available agents. However, its disadvantage is it produces remarkable swelling in the first one to five post-procedure days, injection site pain, skin eruptions, skin discoloration, superficial thrombophlebitis and grave adverse effects such as anaphylactic shock and possible neurological injury [ 2 , 4 ]. Microcystic lesions (< 10 mm) can be managed by doxycycline, sirolimus or surgery, whereas macrocystic lesions can be treated by the stimulation of the lining endothelium by STS, bleomycin, Picibanil (OK‑432) or 60%-100% ethanol [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is established that patients with widespread facial venous malformations have a high incidence of associated intracranial developmental venous anomalies (DVAs) [ 3 ]. Various percutaneous intralesional sclerosing agents like sodium tetradecyl sulfate (STS), bleomycin, doxycycline, ethanol and OK-432 (Picibanil) have been used as first-line treatment for VLMs elsewhere in the body [ 4 ]. We describe a rare case of retro-orbital VLM treated successfully with STS injection and an isolated dural arterio-venous (AV) fistula in the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…15 Common sclerosing agents include sodium morrhuate 5%, sodium tetradecyl sulfate 3%, absolute ethanol, picibanil (OK-423), bleomycin, and tetracyclines. 17 Multiple case series have demonstrated at least early success in treating orbital venous malformations with sclerotherapy, including bleomycin, [3][4][5][6][7][8] ethanol, 3,9,10,15 sodium tetradecyl sulfate, 4,11,12,15 doxycycline, 15 and pingyangmycin. 10,13,14 However, a recent systematic review of the literature, which analyzed 12 studies containing 142 patients with orbital VLMs, found that only 55% of patients experienced complete cure, with 45% experiencing partial cure.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for distensible orbital venous-dominant VLM commonly includes 3 major options: sclerotherapy, surgery, and embolization followed by surgical excision. While some case series have demonstrated initial success in managing venous-dominant VLM with minimally invasive sclerotherapy, [3][4][5][6][7][8][9][10][11][12][13][14] they often require multiple treatments and have a tendency to recur over time. 15 These lesions may also be surgically excised, with or without the assistance of vascular clips, though there is a significant risk of uncontrolled hemorrhage.…”
mentioning
confidence: 99%